O perfil motivacional do docente da rede estadual de ensino fundamental na paraíba - Viana, Júlio Cezar da Câmara Ribeiro (2008)
Willing to know the influence of motivating agents in the behavior of teachers, the target population of the research, specifically on the public elementary schools of the state of Paraíba, this study covered a population composed of 874 professionals, 350 of them being temporary staff and 524 regular personnel. In the prospect of this study this population represents a complex universe to treat the subject motivation, regarding the magnitude of intervenient variables involved in this process which goes all the way from the pedagogical techniques, through the expectations of teachers for their students, to the concern about educational materials, teacher training, improvement of the structural conditions of school and the classroom as a whole, and also the processes of: institutional management, leadership, interpersonal relationships, education policy, availability of resources, among other important issues to deal with in this thematic. The fundamental theories that gave support to the analysis were taken from reports of Herzberg (1972), Maslow (1971), McClelland (1971), McGregor (1973), Vroom (1964) and others who sought in their theories, to show that the actual Work is a great provider of motivation, satisfying the supreme need of growth of human beings; It all was discussed in this study, relating them to the work of professionals linked to the teaching of Paraiba. These authors also tried to demonstrate that the factors that cause satisfaction are determinants of positive human behavior, from answers given by the human intellect. In other words, the feeling of satisfaction is also a need, which serves as a centre of behaviour organization at any given time. In other words, the needs mobilize the resources that each person has, channeling them to reach certain goals or marks. The argument presented here serves to demonstrate that motivation also includes the achievement and the pursuit of growth that leads to the scope of personal satisfaction as part of the dynamics of personal performance in relation to work. This means understanding that the satisfaction with the work derives from the environmental conditions offered by the company and is caused by a motivational factor that result in a particular pattern of positive performance, or above the average performance. In the specific case of professionals in the area of education, for example, efficiency and quality are inseparable attributes and must be present in the effort of every professional, for their students to see the prospect of gaining citizenship as sign of the quality of work developed in each unit of education in this country. The conclusion to which it has been arrived with the analysis of the data is that: in the profile of professional motivational investigated prevails, the need for self-realization, as the wage policy in operation is not enough to supply their basic needs, it turns out that the recompense comes from work itself, the possibility of showing competence, to help educating people and making them able to take place as human beings and as citizens.